Urban Morphology and Development of Mae Hong Son Old City: A Geospatial Analysis for Sustainable Heritage Conservation - O-in, Supharerk (Department of Urban and Regional Planning, Diponegoro University, 2025)
This study investigates the urban morphology and development of Mae Hong Son's old city through geospatial analysis to support sustainable heritage conservation. It focuses on spatiotemporal changes in urban expansion by utilizing aerial photographs, high-resolution satellite imagery, and geospatial techniques including Change Detection and Kernel Density Estimation (KDE), to analyze the city’s development patterns from 1971 to 2023. The results indicate that the built-up area increased significantly from 0.47 km² in 1971 to 9.71 km² in 2023, while the number of buildings grew from 2,855 to 11,948 during the same period. These findings reveal significant physical transformations, primarily driven by economic growth and increased settlement in the early 20th century. Urban growth predominantly occurred in the northern part of the city, constrained by surrounding mountains and rivers. Despite modern urban development, Mae Hong Son has retained its unique identity through a combination of traditional wooden structures and contemporary architecture. The findings emphasize the need to balance modern urban expansion with the preservation of cultural heritage and offer insights for sustainable conservation planning in historic cities and it contributes to understand the historical urban dynamics of Mae Hong Son’s old city and provides recommendations for sustainable heritage conservation planning.